Investigation Of Bacterial Counts In Air At Different Wards Of A Tertiary Care Hospital, Western Rajasthan - Niranjan Sharma & Shivani khullar, Laxmi Rathore*, Dr.P.K. Khatri , Dr.Saroj Meena , Dr.Archana Bora, (International Journal of Scientific Research and Management (IJSRM), 2015)
INTRODUCTION: - Nosocomial infections represent an important cause of morbidity and mortality in population. It has been suggested that many pathogens can survive as bio-aerosols, spread considerable distances and result in infection..Thus, in this study, the basic aim was to investigate bacterial air load of the hospital environment in tertiary care hospital western Rajasthan. METERIAL &METHOD: - Settle plate method is adopted using standard sized MacConkey agar and Blood agar plates.Plates are distributed atvarious distance in the wards like Intensive Care Unit, Critical Care Unit, Post-Surgical ward, Orthopaedic ward and surgical ward and left opened to the air for one hour.Then Colonies of Air Petri Plates are counted for colony forming unit per cubic meter (cfu/m3 ).RESULT:- Microbial Indoor Air Contamination of is observed in this study. Maximum microbial Indoor Air contamination is found in Post Surgical ward (Female) wards i.e. 1062.72 CFU/m3 . Minimum microbial Indoor Air contamination is found in ICU A i.e. 311.35 CFU/m3 . Coagulase negative Staphylococci, Staphylococcus aureus, Micrococcus, Bacillus spp., E. coli, Klebsiella were diagnosed. CONCLUSION: -In conclusion almost all indoor air samples showed higher aerobic bacterial load. So Prevention of contamination risk of nosocomial pathogens and infections stands out as problem that must be weighed in mind.